ANDROID-BASED MOBILE LEARNING MEDIA: DEVELOPING SHORT FUNCTIONAL TEXT MEDIA FOR SEVENTH GRADE STUDENTS - Yulista, Ageng Wulan; Ifadah, Muhimatul; wijayatiningsih, testiana deni; Darwis, Djamaluddin (SEAQIL Journal of Language Education, 2024)
EFL learners had a less enthuastic and  difficult experiences when they studied short fuctional text. So, this current study discussed how to create a mobile phone application for online learning compatible with Android and Windows platforms named short functional text: greeting card. This study also attempted to evaluate the effectiveness of acquiring English language skills using Android-based mobile learning media. This study employed a research and development methodology, which involved nine consecutive stages: identification of potential and challenges, data collection, product design, validation of the design by experts, product testing, initial product revision, trial usage of the product, second product revision, and finalization of the product. The research instruments employed were questionnaires and tests. The data analysis was performed utilizing descriptive statistics and an independent sample T-test. The participants included eighth-grade students who were enrolled at SMP N 4 Purwodadi. Three separate findings were obtained from this inquiry. The validation of media and material specialists was a relevant evaluation of an authentic product, and the viability of using an Android-based mobile learning media product was established. Moreover, the average pre-test and post-test results exhibited a significant significance level, suggesting that the android-based mobile learning media was very effective as a learning medium throughout the learning process. Moreover, the student's perception findings were categorized as positive, with 75.5% indicating their agreement with using Android-based mobile learning media for learning. Using android-based mobile learning media can help students comprehend condensed functional content included in greeting cards, and it can alleviate monotony throughout the learning process.